Interpretando a geomemória dos blocos construtivos das ruínas de São Miguel das Missões (RS, Brasil) - Ferreira, Fabiano Vedooto (2016)
This work is part of the research line Natural Dynamics and Environmental Quality of the Southern Cone from the Program of Graduate Studies in Geography of the Federal University of Santa Maria (PPGGEO/CCNE/UFSM). This work aimed at understanding and interpreting of aspects of geomemory (the memory of geological evolution) contained in the building blocks (geodiversity elements) of the ruins of the archaeological site of São Miguel das Missões and missionary spring, and its importance in water storage, as well as the location and inventory of geosites of Jesuit quarry and Ezequiel Corner. Another aspect addressed here are the (geo)educational strategies as important elements of dissemination and conservation of the region’s geological heritage. The methodology was structured in six items: (1) literature review; (2) fieldtrips; (3) experimental activity geopatrimonial interpretation for undergraduate students; (4) interpretation of geopatrimonial aspects with accessible language to prepare the content of an interpretive panel at the archaeological site of São Miguel das Missões; (5) development of musical parodies on the geomemory of the building blocks of São Miguel das Missões; and (6) integration of the results. The results, in addition to the full understanding of the regional geological evolution, were five musical parodies, contemplating custom interpretative means, and an interpretive panel, considering the non-personal interpretative means. The parodies were composed based on popular songs and specifically representing each region of Brazil, in order to maximize the geographical/geological message of the Missões region of Rio Grande do Sul. The geomemory of the building blocks of the former reduction of the church of São Miguel Arcanjo and missionary spring, as well as geosites of Ezequiel Corner and Jesuit quarry contain an important record of a part of the geological evolution of the Earth, precisely the Botucatu and Serra Geral formations dating back to a past that predates the existence of the human species and is linked the Mesozoic Era. Geopatrimonial interpretation is an indispensable action for geoconservation of geological and cultural heritage of the Missões region of Rio Grande do Sul.